Nighttime warming promotes copper translocation from root to shoot of wheat (Triticum aestivum L.) through enlarging root systems - Qi, Lin; Li, Chunxia; Lai, Lukuan; Kou, Taiji; Deng, Yi (Frontiers in Environmental Science, 2024)
This study aimed to investigate whether and how nighttime warming (NW) influences the copper (Cu) bioaccumulation of wheat (Triticum aestivum L.) under Cu pollution. We examined plant growth, Cu concentration, and antioxidant enzymes of wheat after 6 months of Cu exposure (0, 100, 400, and 800 mg/kg) under NW. The results indicated that, NW of 1.54 °C significantly promoted Cu translocation from root to shoot through an increasing root system under increased Cu treatments (P < 0.05). The Cu contents of grains were significantly increased by NW under 800 mg/kg Cu treatment (P < 0.05). NW decreased superoxide dismutase (SOD) activity under increased Cu treatments (P < 0.05). There were significantly negative correlations between biomass and Cu concentrations of the same part under NW (P < 0.05). The root biomass significantly increased by 51% in NW compared with nonnighttime warming (CK) (P < 0.05). These results provided evidence that wheat might respond to NW by altering their roots so that they were larger, thinner, and longer, suggesting that soil Cu translocation from root to shoot would be accelerated resulting from the expanded roots under elevated temperatures, and thus forewarned the food safety risks of climate change in agricultural ecosystem.